HAKIKAT FONOLOGI DALAM KAJIAN LINGUISTIK - Muhammad Fadhil Uzmi; Aprilla Nurul (Jurnal Sathar, 2024)
Phonology is a branch of linguistics that studies the sounds of language, and the processes of their formation and change. The smallest unit of language that functions, the term phoneme has the ability to distinguish meaning. Phonemes differ based on where they are in the word, such as the first phoneme in the word "makan" and has a different meaning phonetically. Allophones are phonemes that do not change their meaning. Most sounds in Indonesian are classified as egressive sounds or egressive sounds, according to phonetic studies. Furthermore, the formation of clusters, diphthongs, consonants, and vowels. Phonemization is needed in phonetic research to find sounds that contribute to the differentiation of meaning. Therefore, the purpose of phonemization is to determine the phonemic structure of the language and create effective orthography or spelling. And among the phonological symptoms of Indonesian are addition, deletion, change, contraction, analogy, and suprasegmental phonemes.